The Dependence of Gales on Relevant Meteorological Elements in One of the Hottest Regions of China, the Turpan Basin - Zhiqi Xu; Hao Tang; Xiya Zhang; Haibo Hu (Atmosphere, 2023)
The Turpan Basin is one of the hottest regions in China, with high fire potential. The occurrence of gales could roll over trains as well as spread and expand the fire rapidly, posing adverse effects on traffic and fire protection. Therefore, it is important to discuss the frequency and mechanism of gales in Turpan. Based on the observational data of seven stations and ERA5 reanalysis data from 2015 to 2021, this study uses the t-mode principal component analysis using the oblique rotation (T-PCA) method to explore the seasonal differences and related synoptic patterns of gales in the Turpan Basin. The synoptic circulations are divided into nine categories. In types 1, 2, 3, 5, 7 and 9, there are a high-pressure center to the west and a lower-pressure center to the south of Turpan, while in types 4, 6 and 8, there is a strong high-pressure center to the south or northeast of Turpan. When the high-pressure system is located to the west of Turpan, gales are prone to occur, while to the south or northeast, gales seem to be less likely to occur, which is closely related to synoptic patterns and terrain. To the best of our knowledge, this study pioneered the frequency and mechanism of gales in Turpan, which could facilitate gale prevention in the area.